Steps to an ecological jurisprudence: A review of I'm Namen der Natur - Macduff, Ian (Victoria University of Wellington Law Review, 1994)
The author discusses Klaus Bosselmann's book Im Namen der Natur: Der Weg zum okologischen Rechtsstaat (Scherz Verlag, 1992). The book discusses ecological issues and the rebirth of the ecological legal state. Macduff argues that Bosselmann's book is an important book that brings together the traditional and critical lines of argument about legitimacy, the epistemological redirections of contemporary theologians and physicists, the legal issues of rights and sovereignty, a critical history of late industrial society, and a comprehensive analysis of environmental issues. Macduff concludes that the book needs to be seen not just as a book in environmental law but as a model of the kind of synthesis that modern times require. It is a model of jurisprudence in a very real sense, in moving beyond the safe confines of self-referential and narrowly defined intellectual boundaries, to take on the whole of the intellectual moral, scientific and spiritual culture that shapes crisis and its resolution.